2018
DOI: 10.1016/j.ultras.2018.02.007
|View full text |Cite
|
Sign up to set email alerts
|

Resonance analysis of a high temperature piezoelectric disc for sensitivity characterization

Abstract: Ultrasonic transducers for high temperature (200 °C+) applications are a key enabling technology for advanced nuclear power systems and in a range of chemical and petro-chemical industries. Design, fabrication and optimization of such transducers using piezoelectric materials remains a challenge. In this work, experimental data-based analysis is performed to investigate the fundamental causal factors for the resonance characteristics of a piezoelectric disc at elevated temperatures. The effect of all ten tempe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…When an electric field is applied on the surface of the piezoelectric material, the electric dipole moment will be elongated due to the action of the electric field, and the piezoelectric material will elongate along the direction of the electric field in order to resist the change. This process of generating mechanical deformation through the action of an electric field is called the "inverse piezoelectric effect" [1][2][3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…When an electric field is applied on the surface of the piezoelectric material, the electric dipole moment will be elongated due to the action of the electric field, and the piezoelectric material will elongate along the direction of the electric field in order to resist the change. This process of generating mechanical deformation through the action of an electric field is called the "inverse piezoelectric effect" [1][2][3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, many researchers have explored the capability of PWAS for SHM applications, such as the characterization of PWAS [9,10,11,12,13], impact localization [14,15,16,17,18,19], acoustic emission (AE) detection [20,21], and damage detection in isotropic and composite plates [22,23,24,25,26,27]. These studies facilitate the understanding of PWAS-based SHM applications.…”
Section: Introductionmentioning
confidence: 99%
“…It was concluded that the changes in anti-resonance and resonance frequencies have a linear relationship with temperature. In addition, the sensitivity characterization of high temperature piezoelectric transducers was performed by using resonance analysis [11]. Sinclair and Chertov [12] presented a comprehensive literature study of the radiation endurance of a piezoelectric transducer.…”
Section: Introductionmentioning
confidence: 99%